Kendala Penerapan Pembuktian Terbalik dalam Penyelesaian Tindak Pidana Korupsi di Indonesia - Marfuatul Latifah (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2010)
In 2009, Indonesia is a country with the hihest level of corruption in Southeast Asia. It shows that eradication of corruption in Indonesia is less effective. Proof upside down, is expected to be one solution to increase the eradication of corruption. Evidence has been poured upside down in the Act No. 31 of 1999. However, until now has not be applied as a system of evidence in sloving criminal cases of corruption. This paper discusses the obstacles in the implementation of proof reversed in the completion of corruption. Obstacles in the implementation of evidence found on the reverse inequality formulation of proof upside down in Act No. 31 of 1999. Proof inversely regulated without being accompanied by formal law regulating the implementation mechanism of proof its reversed. The importance of these mechanism is that the arrangement of proof reversed a lex specialist of the Penal Code. In additipn, law enforcement officials, not knowing the subtance and how the application of prrof upside sown so that it aslo inhibits the implementation of proof reversed in the completion of corruption.